A comprehensive experimental and numerical study on redistribution of residual stresses by shot peening. (15th January 2016) - Mahmoudi, A.H.; Ghasemi, A.; Farrahi, G.H.; Sherafatnia, K.
Abstract: Shot peening is one of the most effective surface strengthening treatment technologies in which compressive residual stresses are induced beneath the specimen surface. Effects of various factors on the distribution of residual stress profile induced by shot peening have been investigated by many researchers. However, initial residual stresses are one of the important factors which affect the shot peening residual stress. This study is aimed to present comprehensive numerical and experimental study on the effect of initial residual stresses on the shot peened specimen. Initial residual stresses were induced using a four-point bending rig and grinding. Incremental center hole drilling (ICHD) technique was employed to measure residual stresses on bent, ground, shot peened, bent plus shot peened and ground plus shot peened specimens. Numerical analyses of these processes were performed to provide quantitative comparison of different combinations of residual stresses. The comparison with experimental results helped to have a better understanding on how shot peening residual stresses were redistributed. Furthermore, the surface hardness was measured for all specimens. Graphical abstract: Highlights: Redistribution of residual stresses by shot peening has been studied experimentally and numerically. Finite element analyses of random shot impacts provided were combined with bending and grinding simulations. Interesting results were obtained on how the shot peening stresses redistribute tensile or compressive initial stresses. Residual stresses for all cases were experimentally measured.